2012
DOI: 10.1371/journal.pone.0036647
|View full text |Cite|
|
Sign up to set email alerts
|

Identification of Amino Acids Essential for Estrone-3-Sulfate Transport within Transmembrane Domain 2 of Organic Anion Transporting Polypeptide 1B1

Abstract: As an important structure in membrane proteins, transmembrane domains have been found to be crucial for properly targeting the protein to cell membrane as well as carrying out transport functions in transporters. Computer analysis of OATP sequences revealed transmembrane domain 2 (TM2) is among those transmembrane domains that have high amino acid identities within different family members. In the present study, we identify four amino acids (Asp70, Phe73, Glu74, and Gly76) that are essential for the transport … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
62
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(63 citation statements)
references
References 21 publications
1
62
0
Order By: Relevance
“…Based on the results obtained with the three chosen substrates (E17bG, CCK-8, and E3S), it is concluded that cOATPs and hOATPs are qualitatively similar. Such a conclusion is partially supported by the fact that 4 amino acids (Asp70, Phe73, Glu74, and Gly76) located in the transmembrane domain 2 of OATP1B1 are essential to its transport function (Li et al, 2012), and a sequence alignment analysis showed that these four amino acid positions are identical between humans and cynomolgus monkeys for both OATP1B1 and OATP1B3. However, a more quantitative comparison (across different OATPs) requires expression data for each OATP protein in the individual cell lines.…”
Section: Discussionmentioning
confidence: 96%
“…Based on the results obtained with the three chosen substrates (E17bG, CCK-8, and E3S), it is concluded that cOATPs and hOATPs are qualitatively similar. Such a conclusion is partially supported by the fact that 4 amino acids (Asp70, Phe73, Glu74, and Gly76) located in the transmembrane domain 2 of OATP1B1 are essential to its transport function (Li et al, 2012), and a sequence alignment analysis showed that these four amino acid positions are identical between humans and cynomolgus monkeys for both OATP1B1 and OATP1B3. However, a more quantitative comparison (across different OATPs) requires expression data for each OATP protein in the individual cell lines.…”
Section: Discussionmentioning
confidence: 96%
“…Amino acids within TMs have been shown to play important roles in substrate binding, maintenance of protein stability, and correct folding of proteins (Hong et al, 2004(Hong et al, , 2010Gui and Hagenbuch, 2009;Miyagawa et al, 2009;Li et al, 2012). Studies of single nucleotide polymorphisms have also pointed out that mutants located within TMs often result in functional changes (Kalliokoski and Niemi, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Cells in 48-well plates were used for transport measurement as previously described (Li et al, 2012) Cell-Surface Biotinylation and Western Blot. Cell-surface expression of OATP1B1 and its mutants was examined with the membrane-impermeable biotinylation reagent NHS-SS-biotin using a method described previously (Li et al, 2012).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations